PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MATERI VOLUME KUBUS DAN BALOK DENGAN MODEL INKUIRI - Jumriah, Jumriah (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This study aims to improve the activities and results of mathematics learning through the application of guided inquiry models in class V SDN 009 Sangatta Utara. This research is motivated by the low activity and learning outcomes of students in grade V SDN 009 North Sangatta. The results showed that the teacher's activity in learning mathematics about the volume of cubes and beams through the guided inquiry model in cycle I was 48% with moderate criteria, increasing to 71% in cycle II classified as medium criteria and cycle III being 90% classified as high criteria. Student activity at the first meeting showed 28%, the second meeting showed 39%, the third meeting showed 54%, the average value of the activity of the first cycle students showed 40% with low criteria. After an improvement, there was an increase in cycle II, in the second cycle the first meeting of students' activities showed 53%, the second meeting showed 64%, the third meeting showed 78%, the average value of the activities of cycle II students showed 65% with moderate criteria. In the third cycle there was also an increase in the third cycle the first meeting showed 78% student activity, the second meeting showed 89%, the third meeting showed 94%, the average value of the activity of the first cycle showed 87% classified as high criteria. This increase occurs where students always pay attention to their weaknesses and try to improve it seen in the stages of the cycle that there is always an increase. Increased student activity can also affect the increase in student learning outcomes that show an average percentage of cycle I by 53%, cycle II by 68% and cycle III by 79%. From the results of the study showed that the guided inquiry model can increase the activity and learning outcomes of mathematics in class V SDN 009 North Sangatta.